NCoR1 restrains thymic negative selection by repressing Bim expression to spare thymocytes undergoing positive selection. Issue 1 (December 2017) - Wang, Jianrong; He, Nanhai; Zhang, Na; Quan, Dexian; Zhang, Shuo; Zhang, Caroline; Yu, Ruth; Atkins, Annette; Zhu, Ruihong; Yang, Chunhui; Cui, Ying; Liddle, Christopher; et al.
Abstract Thymocytes must pass both positive and negative selections to become mature T cells. Negative selection purges thymocytes whose T-cell receptors (TCR) exhibit high affinity to self-peptide MHC complexes (self pMHC) to avoid autoimmune diseases, while positive selection ensures the survival and maturation of thymocytes whose TCRs display intermediate affinity to self pMHCs for effective immunity, but whether transcriptional regulation helps conserve positively selected thymocytes from being purged by negative selection remains unclear. Here we show that the specific deletion of nuclear receptor co-repressor 1 (NCoR1) in T cells causes excessive negative selection to reduce mature thymocyte numbers. Mechanistically, NCoR1 protects positively selected thymocytes from negative selection by suppressingBim expression. Our study demonstrates a critical function of NCoR1 in coordinated positive and negative selections in the thymus. Thymocytes are screened by two processes, termed positive and negative selections, which are permissive only for immature thymocytes with intermediate avidity to the selecting ligands. Here the authors show that the nuclear receptor NCoR1 suppresses Bim1 to inhibit negative selection and promote thymocyte survival.